The relationship between macroeconomic variable and performance of bond in Malaysia / Nurhidayah Sailan - Sailan, Nurhidayah (2016)
This study explores the interaction between conventional bond toward some key elements in macroeconomic variable which is interest rate, inflation, gross domestic product, openness of economy and money supply for the case in Malaysia. The purpose of this research is to study on the performance of conventional bond in Malaysia from 2007 Q1 to 2014 Q4. Apart from that, this study wants to know about the performance of bond in Malaysia is a very sensitive or not toward the changes in the macroeconomic variables that have been chosen. This research has employed multiple Ordinary Least Square (OLS) regression model to study on the performance of conventional bond and economic variables in Malaysia.